2005
DOI: 10.1007/s10522-005-4907-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel -209A/G MT2A Polymorphism in Old Patients with Type 2 Diabetes and Atherosclerosis: Relationship with Inflammation (IL-6) and Zinc

Abstract: Vascular complications, including ischaemic cardiomyopathy, are the major causes of death in old diabetic patients. Chronic inflammation due to high IL-6 production occurs in type 2 diabetes (NIDDM) and atherosclerosis. High levels of IL-6 are associated with hyperglycaemia, dyslipidemia and provoke insulin resistance. In ageing and inflammation, IL-6 affects Metallothionein (MT) homeostasis, which in turn is involved in zinc turnover. Zinc deficiency is an usual event in ageing, inflammation, type 2 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 27 publications
(27 reference statements)
1
64
1
2
Order By: Relevance
“…Furthermore, this mutation may directly interfere with the functions of zinc in cellular signal transduction because it attenuates the release of zinc in response to nitric oxide (Cipriano et al 2006). Similarly a mutation in the MT2A promoter is associated with low plasma zinc, higher blood glucose levels, and risk of atherosclerosis and ischemic cardiomyopathy among DM patients (Giacconi et al 2005). The above data suggests that individuals with IL6 and MT mutations may have higher optimal zinc intake requirements.…”
Section: Zinc and Insulin Signaling In Diabetes Mellitus And Dementiamentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, this mutation may directly interfere with the functions of zinc in cellular signal transduction because it attenuates the release of zinc in response to nitric oxide (Cipriano et al 2006). Similarly a mutation in the MT2A promoter is associated with low plasma zinc, higher blood glucose levels, and risk of atherosclerosis and ischemic cardiomyopathy among DM patients (Giacconi et al 2005). The above data suggests that individuals with IL6 and MT mutations may have higher optimal zinc intake requirements.…”
Section: Zinc and Insulin Signaling In Diabetes Mellitus And Dementiamentioning
confidence: 97%
“…Zinc supplementation can also improve glycemic control in patients with diabetes mellitus (DM) (Jayawardena et al 2012) and may benefit a large portion of the aging population (Maylor et al 2006). However several polymorphisms that affect zinc homeostasis have been identified, future research is needed to understand how these mutations may alter dietary zinc requirements and the efficacy of zinc supplementation to prevent or treat major chronic diseases that affect the aging population (Giacconi et al 2005;Xu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, feeding the body with the adequate requirement of zinc can result in a proper antiinflammatory response which may be pivotal to reach longevity severe infections and atherosclerosis. The main results of the project confirmed a strong contribution of MT genetic variants in regulating zinc homeostasis and perhaps its dietary requirements as well as their relevance in longevity and in some age-related pathologies [34,57,95,98]. Moreover, it has been confirmed that IL-6 -174 polymorphisms can be used to identify old subjects with higher risk to develop zinc deficiency [98,108].…”
Section: Resultsmentioning
confidence: 56%
“…The recent discovery of novel polymorphisms of MT2A and MT1A supports this assumption. Indeed, old subjects carrying AA genotype for MT2A polymorphism display low zinc ion bioavailability, chronic inflammation by high IL-6 and altered lipid assessments, with subsequent elevated risk for atherosclerosis and diabetes type II [57]. By contrast, polymorphism corresponding to A/C (Asparagin/ Threonin) transition at +647 nt position in the MT1A coding region is the most involved in the women longevity [34].…”
Section: Zinc-mt Gene Interactionmentioning
confidence: 99%
See 1 more Smart Citation